(untitled) (Research, Society and Development, 2020)
Objectives: To discuss the current state of publications on obstetric care for asymptomatic women for COVID-19 and to point out the contributions of obstetric nursing to the safe care of parturients and newborns in the context of the pandemic. Method: Systematic review based on Cochrane, Embase, BVS; MEDLINE, PubMed, CINAHL and Scopus, to raise publications that answered the question: What are the recommended care measures for assisting asymptomatic women for COVID-19 during childbirth and the puerperium? Results: 36 studies were surveyed, but only 2 met the eligibility criteria. It was found that the publications focus on assistance to pregnant women, parturients and postpartum women symptomatic and / or positive for COVID-19. However, the reality of Brazilian health services imposes challenges for safe obstetric care due to the lack of PPE, the absence of mass testing and the architecture specificities for the maternity hospitals. These challenges may imply an increased risk of spreading the virus in these places and exposure to healthy pregnant women and health professionals. In this context, in line with the actions to combat COVID-19, we point out guidelines for respectful care for women’s rights and insurance for parturients, newborns, mothers, companions and health professionals within the scope of obstetric care services. Conclusion: The set of care proposed for the differents levels of health care has the potential to contribute to obstetric nursing care in the current Brazilian epidemiological scenario, without losing sight of the importance of humanization, quality and safety.